The Determinants of Paddy Field Conversion in Timor Island, East Nusa Tenggara Province (NTT) - Prischa Lulan; Dwidjono Hadi Darwanto; Slamet Hartono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2017)
The objectives of this research are: (1) to investigate the trend of paddy fields on Timor Islandand (2) to know the determinants of the conversion of paddy fields on Timor Island. TimorIsland consists of several districts such as Kupang District, South Central Timor District(TTS), North Central Timor District (TTU), Belu District and Kupang City. In fact, theyare the main rice-producing areas in the Timor Island, so they have an important role in thesupplying sufficient for locals. However, the regions are slowly started to be converted tonon-paddy-field use such as new settlements and other infrastructure development along withthe current economic development. The basic method used in this research was descriptiveanalysis and the location of research was determined purposively because this locationwas based on the consideration that there was a high growth of non-agricultural sectors inTimor Island; making it vulnerable to the reduction of paddy field area. The data used wassecondary data (2005-2014). The results showed that (1) the trend of rice field in Timor Islandis not significant with time variable. (2) The analysis of determinants of paddy field area inTimor Island using multiple linear regression with Ordinary Least Square (OLS) methodindicated that the factors affecting the conversion of wetland in Timor Island significantlyare the variable of building area and the number of industries.